1991
DOI: 10.1007/bf00114163
|View full text |Cite
|
Sign up to set email alerts
|

A critical look at experimental evaluations of EBL

Abstract: Abstract. A number of experimental evaluations of explanation-based learning (EBL) have been reported in the literature on machine learning. A close examination of the design of these experiments reveals certain methodological problems that could affect the conclusions drawn from the experiments. This article analyzes some of the more common methodological difficulties, and illustrates them using selected previous studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
15
1
Order By: Relevance
“…We applied both tests to the speedup learning data set taken from Etzioni (1990a) and have shown that most of the differences observed are statistically significant (see, in particular, the results of our extended signed rank test in table 6). We believe that this approach helps to allay the concerns regarding the use of resource bounds raised by Segre et al (1991). Finally, although we have focused on speedup learning data, we note that our methodology can be used to analyze any quantitative comparison between two systems on a common set of problems.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We applied both tests to the speedup learning data set taken from Etzioni (1990a) and have shown that most of the differences observed are statistically significant (see, in particular, the results of our extended signed rank test in table 6). We believe that this approach helps to allay the concerns regarding the use of resource bounds raised by Segre et al (1991). Finally, although we have focused on speedup learning data, we note that our methodology can be used to analyze any quantitative comparison between two systems on a common set of problems.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent paper, Segre et al (1991) argue that the experimenter's choice of time bound can influence the results of the experiment. Segre et al illustrate this point with a hypothetical example reproduced in tables 1 and 2.…”
Section: Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar comparisons in the past have been done using cumulative time graphs [45], but Segre et al [55] argue that such comparisons could be misleading because changing the time limit can change the results. To avoid this problem, the total time expended solving all of the problems is graphed against the CPU time bound.…”
mentioning
confidence: 86%
“…We used the number of problems solved within the assigned resource limit as an additional measure of performance. As Segre et al (1991) point out, comparisons based on these measures may be sensitive to the values of the resource limits, and inconclusive when some of the problems are not solved within the assigned resource limits. Figure 4 shows FAILSAFE-2's performance in the blocks world domain.…”
Section: Testing the Effectiveness Hypothesismentioning
confidence: 99%